Motivating Women to Travel in India: Embodying Safety as an Organizational Purpose - Chhajer, Raina; Lal, Vedika; Tandon, Ankita (Frontiers in Psychology, 2022)
Safety concerns are a key factor that demotivate women from travelling. Tourism organizations are yet to develop approaches to address this comprehensively. Employing the case study design, this study describes how an Indian tourism organization adopted safe women travel as its purpose to reduce women’s safety risk perceptions and motivated them to travel. Nine qualitative interviews were conducted with key stakholders including co-founders, employees, customers, and vendors. Data was analyzed using thematic analysis resulting in the identification of purpose as a pull factor. Themes of defining, communicating, embodying purpose and its resulting influence, were identified. Through this process, the organization was able to positively impact perceptions of safety, enhance women’s travel motivation, and develop long term associations with all stakeholders. An actionable framework for implementing purpose was developed that can be used to align tourism organizations’ practices and activities.